A review of the uses of virtual reality in engineering education. Issue 3 (22nd April 2020) - di Lanzo, Jaiden A.; Valentine, Andrew; Sohel, Ferdous; Yapp, Angie Y. T.; Muparadzi, Kudakwashe C.; Abdelmalek, Merkorios
Abstract: The use of virtual environments as pedagogical tools within the domain of education has become an increasingly popular phenomenon over the last few decades especially. However, the uses and effects of virtual environments as pedagogical tools within the specific domain of engineering education have not been explored in extensive detail. The limited body of current research regarding the uses of virtual environments in engineering education affords a unique opportunity. This review provides an overview and synthesis of the uses of virtual reality within the domain of engineering education through the systematic analysis of journal articles and conference proceedings published across two databases ( IEEE Xplore and Scopus ) between 2015 and 2019. In summary, 17 studies were analysed utilising a systematic approach and using a coding scheme including four main categories and 12 binary items. The findings indicate an escalation in the use of virtual classroom environments as supplementary to traditional teaching environments, as well as reported substantial benefits to cognitive and skill‐based learning outcomes. The findings suggest that evaluation metrics and processes that lack clarity, together with unrealistic virtual scenarios and small evaluation sample sizes, may confound comparison and, hence, the reported substantive and beneficial use of virtual reality environments in engineering education. Scholars and educators within the domain of engineering education should continue investigating the uses and merits of virtual reality environments as pedagogical tools, taking these issues into consideration.